PERBANDINGAN SISTEM ADMINISTRASI PUBLIK DALAM PENGELOLAAN EKSPOR DAN IMPOR ANTARA INDONESIA DAN CINA - Nofita Ningsih; Aminullah (As-Sulthan Journal of Education, 2026)
This study compares public administration systems in managing exports and imports between Indonesia and China as a key factor supporting international trade. Using a qualitative, descriptive-comparative approach through literature review, the study analyzes institutional structures, administrative procedures, and government roles in both countries. The results indicate that Indonesia implements an administrative system involving multiple institutions, integrated through digitalization, such as the Indonesia National Single Window (INSW), while China uses a more centralized system with strong authority in one central institution. These differences impact efficiency, policy consistency, and ease of service for businesses. The study concludes that institutional structure and inter-institutional coordination significantly determine the effectiveness of export-import administration. These findings can serve as a reference for Indonesia in improving its international trade competitiveness.